2021
DOI: 10.1002/pds.5247
|View full text |Cite
|
Sign up to set email alerts
|

Trends in strong opioid prescribing in Ireland: A repeated cross‐sectional analysis of a national pharmacy claims database between 2010 and 2019

Abstract: Purpose: Significant increases in opioid utilisation have been reported in many countries in recent decades. This study investigated strong opioid prescribing in Irish General Medical Services (GMS) patients over a 10-year period.Methods: A retrospective repeated cross-sectional analysis of a national pharmacy claims database between January 2010 and December 2019 was conducted. Strong opioid prescribing in GMS patients was evaluated, including by route of administration, age (16-64 years and ≥65 years) and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 38 publications
(124 reference statements)
6
29
3
Order By: Relevance
“…A recent Irish study of strong opioids showed increases continued from 2015 to 2019, particularly for oxycodone and tapentadol. 6 By comparison, research in England found items per 1000 population increased from 578 in 2000 to 762 in 2015 (31% increase), and a 115% increase in OMEs (199 000–428 000). 4 Other international estimates include 464 000 OMEs per 1000 population in British Columbia, Canada, 12 and 543 400 per 1000 population in the United States, 17 although with noted variation between provinces/states.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A recent Irish study of strong opioids showed increases continued from 2015 to 2019, particularly for oxycodone and tapentadol. 6 By comparison, research in England found items per 1000 population increased from 578 in 2000 to 762 in 2015 (31% increase), and a 115% increase in OMEs (199 000–428 000). 4 Other international estimates include 464 000 OMEs per 1000 population in British Columbia, Canada, 12 and 543 400 per 1000 population in the United States, 17 although with noted variation between provinces/states.…”
Section: Discussionmentioning
confidence: 97%
“…The decline in morphine concurrent with growth in newer opioids has been reported in other studies, as prescribers switch to these as the strong opioid of choice. 4 , 6 , 12 Promotion and marketing of newer opioids and opioids formulations may have contributed to uptake of these agents. 13 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations